Job Satisfaction Of Go-jek Drivers in South Tangerang Based on Compensation and Work Stess - Husainah, Nazifah; Gofur Ahmad , Abdul; Suryaningrum, Ira Puspitadewi; Faqih, Annas Al (Jurnal Manajemen, Akuntansi, Ekonomi, 2025)
This study aims to find out and analyze the effect of Compensation (X1) and Work Stress (X2) on Gojek's Job Satisfaction in South Tangerang (Y).This type of research uses quantitative research that is associative using primary data where there are two variables, namely Compensation and Work Stress as independent variables and Job Satisfaction as bound variables (Dependent). The population in the study was 125 respondents. The sample extraction technique in this study uses the maholtra method. In this study, data collection was used a questionnaire. Technical Data analysis in this study uses Validity Test, Reliability Test, Classical Assumption Test (Normality Test, Heteroscedasticity Test, Multicollinearity Test), Multiple Linear Regression Analysis, Determination Coefficient Analysis, t-Test and F Test.The results of this study show that compensation has a positive and significant effect on job satisfaction with a t-value of >4,391 > 1,979 and a significance value of 0.000 < 0.05, Work Stress has a positive and significant effect on job satisfaction with a t-value of > t table of 5,094 > 1,979 and a significance value of 0.000 < 0.05,  Compensation and work stress together had a positive and significant effect on job satisfaction with F calculated > F table which was 64,043 > 3.07 and a significant value of 0.000 < 0.05.